Optimalisasi Peluang Dan Tantangan Ekonomi Islam Dalam Menghadapi Masyarakat Ekonomi Asean - Zainal Arif (Al Maal: Journal of Islamic Economics and Banking, 2019)
The ASEAN leader have agreed to conduct coorperation in the field of economics. Called the ASEAN Economic Community or (MEA). The MEA is mutual agreement to integrate a various ASEAN countries (Indonesia, Singapura, Malasyia, Brunai Darussalam, Thailand, Kamboja, Vietnam, Laos and Myanmar). Where the countries has a socio-culture background, politic, economic, ideological interest into ASEAN community. As an integrated ASEAN is expected to cooperate in improving efficiency and spuring the economic competitiveness of ASEAN wich is indicated through the free flow: goods, services, investment, labor and capital. MEA is a challenge for Islamic economy at the same give a opportunities for the future of Islamic economy, Islamic finance. Because the Sharia bussines will evolve across the ASEAN countries.